2023
DOI: 10.3390/jmse11071363
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Pore Structure Evolution in the Triassic Chang 7 Shale, Ordos Basin, China: Experimental Simulation of In Situ Conversion Process

Abstract: The reservoir properties of low–medium-maturity shale undergo complex changes during the in situ conversion process (ICP). The experiments were performed at high temperature (up to 450 °C), high pressure (30 MPa), and a low heating rate (0.4 °C/h) on low–medium-maturity shale samples of the Chang 7 Member shale in the southern Ordos Basin. The changes in the shale composition, pore structure, and reservoir properties during the ICP were quantitatively characterized by X-ray diffraction (XRD), microscopic obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Firstly, the capacity/resistance ratio (CRR) and the time of arrival at the boundary (t BDF ) can be calculated by Equations ( 5) and (7). Meanwhile, the given constant rate is q c to be this value.…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the capacity/resistance ratio (CRR) and the time of arrival at the boundary (t BDF ) can be calculated by Equations ( 5) and (7). Meanwhile, the given constant rate is q c to be this value.…”
Section: Model Developmentmentioning
confidence: 99%
“…where m(p) is the pseudo-pressure, ki is the intrinsic permeability, * ( ) z p is the pressur dependent compressibility factor. Based on the above definitions and equations, a new analytical calculation metho can be obtained to perform pressure analysis of onshore and offshore shale gas reservoi under constant-rate condition considering interlayer cross-flow and thin sandstone laye Firstly, the capacity/resistance ratio (CRR) and the time of arrival at the boundary (tBD can be calculated by Equations ( 5) and (7). Meanwhile, the given constant rate is qc to this value.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…China has focused geological studies on shale oil since 2010, especially on key technological breakthroughs and exploration dimensions [9][10][11][12]. Moreover, in 2023, there were over 2500 horizontal wells, and the shale oil yield reached 342 × 10 4 t. However, global shale oil exploration and development practices have revealed that the existing horizontal well and hydraulic fracturing techniques are not able to achieve the cost-effective development of immature to low-moderate-maturity shale hydrocarbon reserves [13][14][15][16][17]. The main reasons for this are the low maturity of the organic matter in such shale layers, the low hydrocarbon conversion rate of the convertible organic matter, undeveloped organic pores, poor reservoir connectivity, and a low gas-oil ratio (GOR).…”
Section: Introductionmentioning
confidence: 99%
“…Hubbert proposed a peak oil production theory in 1956, which led many countries and companies to target immature to low-moderate-maturity shale oil to increase hydrocarbon production [18]. In this respect, a number of international oil companies, such as Shell, ExxonMobil, and Total, have initiated research on the in situ conversion of shale oil and have conducted field experiments on various in situ conversion techniques [14,15,19,20]. In addition, the in situ electrical heating conversion technology proposed by Shell in the 1960s is the most prominent technique to date.…”
Section: Introductionmentioning
confidence: 99%